Effects of induced trench configuration and EPS geofoam density on the HDPE pipe behavior - Akinay, E.; Kilic, H. (EMERALD GROUP PUBLISHING LTD, 2023)
The effects of induced trench configuration and stiffness of compressible inclusion on the HDPE pipe behavior were investigated through full-scale laboratory tests. Two pipe-compressible inclusion configurations ( compressible inclusion over the pipe crown and the pipe covered with compressible inclusion ) were tested and EPS Geofoam with 10 and 15 kg/m(3) nominal density was used as compressible inclusion. To simulate geostatic stresses imposed by high embankment fill, the surcharge stress up to 200 kPa was applied on the surface of the burial medium. Comprehensive instrumentation was implemented to measure the pipe deflections, soil stresses on the pipe, and soil settlements in the pipe zone. Considering the pipe behavior and cost-efficiency together, the configuration in which one EPS Geofoam panel with 10 kg/m(3) nominal density is placed over the pipe crown arises as the optimal solution for the induced trench HDPE pipe. This solution provided a reduction in the vertical stress at the pipe crown up to of 76% and in the horizontal stress at the pipe springline up to of 65%. The vertical and horizontal pipe deflections are reduced by 87% and 60%, respectively, under 200-kPa surcharge stress. i.e., overburden pressure imposed by a 10-m-high embankment fill.
Keywords: Geosynthetics; HDPE Pipe; EPS Geofoam; Full-scale test; Soil arching; Instrumentation; LABORATORY FACILITY; STRUCTURAL RESPONSE; CONSTITUTIVE MODEL; FIELD PERFORMANCE; EARTH PRESSURE; BURIED PIPES; INSTALLATIONS; REDUCTION; DESIGN; Engineering; Geology; Materials Science